Consequences of departure from normality on the properties of calibration estimators - Shalabh; Helge Toutenburg (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2005)
This paper considers the classical and inverse calibration estimators and discusses the consequences of departure from normality of errors on their bias and mean squared error properties when the errors in calibration process are small.
urn:nbn:de:bvb:19-epub-1810-4
Keywords: 519